Family abduction in a national sample of US children. (May 2017) - Finkelhor, David; Henly, Megan; Turner, Heather; Hamby, Sherry
Abstract: This study examined the prevalence and characteristics of family abduction episodes occurring in a nationally representative sample of US children ages 0–17. It drew on the experiences of 13, 052 children and youth from the aggregation of three cross-sectional waves (2008, 2011, and 2014) of the National Surveys of Children Exposed to Violence. The overall prevalence rate was 4.1% for a lifetime and 1.2% for a past year episode. Rates were higher for younger than older children. Parents constituted 90% of the abductors with females outnumbering males 60% to 40%, although men outnumbered women as perpetrators for certain types of abductions. A bit less than half of the episodes (43%) were reported to police. The experience of a lifetime family abduction had an independent association with traumatic stress symptoms independent of exposure to other kinds of victimization including child maltreatment and witnessing family violence.